EDUCATIONAL GAME STORY ADVENTURE OF CAKRA INDEPENDENCE HISTORY VERSION - Rizki, Muhammad; Wijayanti, Esti; Chamid, Ahmad Abdul (Tekmapro, 2025)
The educational game “Story Adventure Of Cakra” with the theme of Indonesian independence history is designed to improve students’ understanding and interest in learning, especially among students in grades 3 and 4 of elementary school, through an interactive and fun approach. This game was created using the Game Development Life Cycle (GDLC) method and the Construct 3 engine, with a focus on learning history through adventure gameplay and a quiz system. This study uses a qualitative approach involving students in grades 3 and 4 of elementary school and history teachers as research subjects. Data collection was carried out through interviews, participatory observations, and literature studies. The results of blackbox testing showed that all game features, including the navigation system, gameplay, and quiz-based evaluation features, functioned well. In addition, trials with students and teachers showed that this game was able to attract students’ attention and increase their motivation to learn the history of Indonesian independence. Overall, “Story Adventure Of Cakra” has succeeded in becoming an innovative learning alternative in Indonesian history education. This game has a positive impact on students’ understanding, combines elements of entertainment and education, and supports the creation of a fun and effective learning experience. With its potential, it is hoped that this game can continue to be developed to support history learning at various levels of education. Kata Kunci: Game edukasi, Sejarah Kemerdekaan, GDLC, Construct 3, Pembelajaran Interaktif.